2021
DOI: 10.3390/su13115795
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Model of Construction Projects Executed in Random Conditions with the Overlapping Construction Works

Abstract: Reducing the duration of construction works requires additional organizational measures, such as selecting construction methods that assure a shorter realization time, engaging additional resources, working overtime, or allowing construction works to be performed simultaneously in the same working units. The simultaneous work of crews may affect the quality of works and the efficiency of construction processes. This article presents a simulation model aimed at assessing the impact of the overlap period on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Faghihi et al compared existing studies and found that the research on optimizing construction scheduling mainly focuses on the temporal aspects of the project schedule [4]. However, the importance of working space availability at an assigned location tends to be ignored [5][6][7][8][9].…”
Section: Literature Review 21 Takt-time Planning Methodsmentioning
confidence: 99%
“…Faghihi et al compared existing studies and found that the research on optimizing construction scheduling mainly focuses on the temporal aspects of the project schedule [4]. However, the importance of working space availability at an assigned location tends to be ignored [5][6][7][8][9].…”
Section: Literature Review 21 Takt-time Planning Methodsmentioning
confidence: 99%
“…Fixed cost perusahaan juga dipercaya akan berkurang seiring dengan penghematan yang diperoleh dari penerapan metode fast-track. Hal ini juga merupakan kelebihan dari metode fast-track dibandingkan dengan metode lainnya seperti crashing atau time cost trade off (TCTO) dimana upaya percepatan terhadap jadwal kerja akan berdampak pada perlunya penambahan sumber daya dan meningkatnya pembiayaan proyek (Widyo Kisworo & Sri Handayani, 2017) (Kim et al, 2012) (Biruk & Rzepecki, 2021) (Abuwarda & Hegazy, 2019).…”
Section: Pendahuluanunclassified
“…The construction process is unique and non-replicable (Liu et al, 2019) due to project-specific construction conditions (Biruk and Rzepecki, 2021). Therefore, it is not appropriate to directly compare actual construction processes (i.e., processes of constructing projects with the same design using different methods).…”
Section: Comparative Analysismentioning
confidence: 99%